Assessment of Thymic Output Dynamics After in utero Infection of Mice With Coxsackievirus B4 - Halouani, Aymen; Jmii, Habib; Bodart, Gwennaëlle; Michaux, Hélène; Renard, Chantal; Martens, Henri; Aouni, Mahjoub; Hober, Didier; Geenen, Vincent; Jaïdane, Hela (Frontiers in Immunology, 2020)
The thymus is the main organ of the lymphatic system, in which T cells undergo a rigorous selection to ensure that their receptors (TCR) will be functional and will not react against the self. Genes encoding for TCR chains are fragmented and must be rearranged by a process of somatic recombination generating TCR rearrangement excision circles (TRECs). We recently documented Coxsackievirus B4 (CV-B4) infection of Swiss albino mouse thymus in the course of in utero transmission. In the current study, we intended to evaluate thymic output, in this experimental model. For this purpose, pregnant Swiss albino mice were inoculated with CV-B4 at day 10 or day 17 of gestation, and thymus and spleen were sampled from offspring at different time points, and then subjected to quantification of TRECs molecules and Ptk7 gene expression. Results showed a pronounced effect of in utero CV-B4 infection on the thymus with an increase in the cellularity and, consequently, the weight of the organ. sj and DβTRECs analysis, by real-time PCR,revealed a significant decrease following CV-B4 infection compared to controls, a decrease which gets worse as time goes by, both in the thymus and in periphery.Those observations reflect a disturbance in the export of T cells to the periphery and their accumulation within the thymus. The evaluation of Ptk7 transcripts in the thymus, for its part, showed a decrease in expression, especially following an infection at day 10 of gestation, which supports the hypothesis of T cells accumulation in a mature stage in the thymus. Disruption in thymic export may indeed interfere with T cell maturation, we speculate that this may lead to a premature release of T cells and the possibility of circulating autoreactive or proliferation-impaired T cell clones.